우리나라 성인 흡연자의 전자담배 이용경험과 금연행태의 관련성 - 이윤노; Yoon Noh Lee; 김복미; Bokmi Kim; 민인순; In Soon Min; 함명일; Myung-il Hahm (Health policy and management, 2017)
Background: Electronic cigarette (e-cigarette) has rapidly increased. Even though e-cigarettes are actually not smoking cessation alternative supplies, some people perceive them as smoking cessation alternative supplies. The purpose of this study is to identify the relationship between e-cigarette experiences and smoking cessation behaviors among Korean adults. Methods: Cross-sectional data was collected from 7,550 participants of Korea National Health and Nutrition Examination Survey in 2014. A total of 867 participants who were current smokers were enrolled in this study. Multi-variable logistic regression analysis were performed to identify the relationship between the smoking cessation behavior and the e-cigarette experience. Results: The e-cigarette experience rate of current smokers was 22.1%. The e-cigarette experience rate was higher in groups with the higher income, the higher education level, and the white collar jobs. Smokers with experience of smoking cessation (odds ratio [OR], 3.03; 95% confidence interval [CI], 1.67 to 5.76) and with intention to smoking cessation in the future (OR, 1.59; 95% CI, 1.05 to 2.43) were more likely to experience the e-cigarette. Especially, smokers who used smoking cessation alternative supplies were more likely to experience the e-cigarette than smokers who did not use it (OR, 2.87; 95% CI, 1.59 to 5.18). Conclusion: We confirmed that e-cigarette experiences were associated with smoking cessation experience, smoking cessation plan, and use of smoking cessation aid among smokers in Korea. Additional studies should be continued to confirm whether e-cigarette are continuously influencing the smoking cessation of current smokers in South Korea as one of the smoking cessation alternative supplies.